Can the inferior vena cava collapsibility index be useful in predicting hypotension during spinal anaesthesia in a spontaneously breathing patient? A mini fluid challenge - Jaremko, Inna; Mačiulienė, Asta; Gelmanas, Arūnas; Baranauskas, Tautvydas; Tamošiūnas, Ramūnas; Smailys, Alfredas; Macas, Andrius (Acta medica Lituanica, 2019)
The study was performed at the Department of Orthopaedics and Traumatology of the Kauno Klinikos Hospital of Lithuanian University of Health Sciences. Background. Intravascular fluids are empirically administered to prevent hypotension induced by spinal anaesthesia. Ultrasound measurements of the inferior vena cava (IVC) and the IVC collapsibility index (IVC-CI) is a non-invasive method to evaluate the intravascular volume status. The aim of the study was to identify the prognostic value of the IVC collapsibility index in spontaneously breathing patients to predict severe intraoperative hypotension. Materials and methods. Sixty patients undergoing elective knee arthroplasty under spinal anaesthesia were included in the prospective study. The diameters of IVCex, IVCin, and IVC-CI were measured before and 15 min after spinal anaesthesia when administration of 500 ml of normal saline using infusion pump was finished. The haemodynamic parameters (heart rate, systolic, diastolic, and mean blood pressures, breathing rate) were collected. Results. Severe arterial hypotension was noticed in 18.3% of the patients. No statistically significant differences were detected between changes in IVCex, IVCin, and IVC-CI comparing hypotensive and non-hypotensive patients at the baseline and after the interventions (p > 0.005). According to receiver operating characteristic (ROC) analysis, IVC-CI is not effective in the prediction of severe hypotension during spinal anaesthesia in spontaneously breathing patients: the area under the ROC curve for IVC-CI was 0.05. Conclusions. IVC-CI is not an effective predictor of severe hypotension after induction of spinal anaesthesia followed by normal saline administration in spontaneously breathing patients undergoing elective knee arthroplasty. More trials, including different patient subgroups, will be needed.
Keywords: spinal anaesthesia; hypotension; fluid therapy; inferior vena cava; collapsibility index